Website Hypertension Self Assesment Mendeteksi Pengetahuan, Sikap Pasien dalam Menjaga Tekanan Darah - Islah Wahyuni; Ingelia Ingelia; Firna Asri Melani; Sondang Elizabeth Tinambunan; Dila Safitri; Nurhaliza Indah Reteh; Nurul Fadillah; Dea Nisti; Annisa Triwahyuni; Putri Aprianti Sagala; Muthia Dzuwelda; White Asmara Gulo; Mutia Ade Putri; Bella Sari Andri Putri; Anabella Bhanuawati; Yolanda Yolanda; Windhary Triana Putri; Tengku Susheillawati; Mita Astuti (Jurnal Kebidanan Harapan Ibu Pekalongan, 2024)
The incidence of hypertension in Indonesia is 34.1% of the population. Silent killer is the name given to hypertension as it is a global health problem that is increasing significantly. Hypertension is the main cause of many serious diseases, such as heart disease and stroke. Knowledge, understanding and early prevention efforts regarding hypertension are very important to improve quality of life and reduce the burden of disease in Indonesia and the world. The purpose of the study was to identify attitudes, behaviors and satisfaction, in maintaining healthy blood pressure using the hypertension self-assessment website. In this study using correlation analysis method. Correlation analysis is a quantitative data analysis method that aims to determine whether or not there is a relationship between variables so that it can make it easier to determine and predict the value of other variables. The sample of this study was taken randomly in the range of adolescents to the elderly at Puskesmas Rumbai Pekanbaru with a total of 45 samples. It was found that all respondents were satisfied with the use of the hypertension self-assessment website in detecting hypertension problems, namely 100%, detected most of the respondents' attitudes were negative in maintaining healthy blood pressure, namely 33 people (73.3%) and detected all respondents' behavior was poor in maintaining healthy blood pressure, namely 45 people (100%). The use of the Hypertension Self-Assessment Website is very good in detecting patient attitudes and behaviors in assessing patients' preventive efforts against their hypertension problems, and health workers can help recommend it to patients during visits to health facilities, and can assist health workers in monitoring and educating the public to maintain healthy blood pressure.